2022
DOI: 10.1038/s41419-022-04584-4
|View full text |Cite
|
Sign up to set email alerts
|

Stat4 rs7574865 polymorphism promotes the occurrence and progression of hepatocellular carcinoma via the Stat4/CYP2E1/FGL2 pathway

Abstract: Although there are many studies on the relationship between genetic polymorphisms and the incidence of diseases, mechanisms are rarely known. We report the mechanism by which signal transducer and activator of transcription 4 (stat4) rs7574865 promotes the occurrence and progression of hepatocellular carcinoma (HCC). We found that the GG genotype at stat4 rs7574865 was a risk genotype, and STAT4 levels in serum and peritumoral tissue from HCC patients with the GG genotype were significantly higher than those f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…El Sharkawy et al have recently confirmed that a risk STAT4 SNP in a Caucasian population is associated with a greater rate of fibrosis and inflammation in HBV patients [22]. The same effects have been described in Asian populations [23,34,36,37]. It is also possible that inflammatory mechanisms leading to different immune active mechanisms related to STAT activation or inactivation are present in certain populations compared to others, affecting HCC risk [20,46,47].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…El Sharkawy et al have recently confirmed that a risk STAT4 SNP in a Caucasian population is associated with a greater rate of fibrosis and inflammation in HBV patients [22]. The same effects have been described in Asian populations [23,34,36,37]. It is also possible that inflammatory mechanisms leading to different immune active mechanisms related to STAT activation or inactivation are present in certain populations compared to others, affecting HCC risk [20,46,47].…”
Section: Discussionmentioning
confidence: 82%
“…STAT4 functions as a mediator of immunity and tumor growth as an important member of the JAK-STAT pathway. It has been associated with autoimmune diseases [ 31 , 32 ] and malignancies such as lung, colon, and breast cancer [ 22 , 23 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the rs7574865 polymorphism of the STAT4 gene is a G > T change in the third intron, which has been associated with its TT polymorphic genotype with the increased presence of autoimmunity. In patients with SLE, the polymorphic variant has been identified as being associated with increased susceptibility to presenting with the disease, as well as an increased risk of presenting positive autoantibodies [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%